Кулонова сума та кулонова енергія ядра 7Lі - Тімченко, І.С.; Timchenko, I.S. (Харків: ХНУ імені В. Н. Каразіна, 2019)
Timchenko I.S. Coulomb sum and Coulomb energy of the 7Li nucleus. – Manuscript. Thesis for the candidate degree of physical and mathematical sciences by specialty 01.04.16 – Physics of Nucleus, Elementary Particles and High Energies. – Institute of high-energy physics and nuclear physics National Science Centre "Kharkov Institute of Physics and Technology", National Academy of Sciences of Ukraine; V. N. Karazin Kharkov National University, Ministry of Education and Science of Ukraine, Kharkov, 2019. In the thesis, a study of the Coulomb sum and the Coulomb energy of the 7Li nucleus based on inclusive electron scattering data is presented. As a result of this study, values of the longitudinal response function RL(qc,ω) and the Coulomb sum SL(q) for the 7Li nucleus for the constant momentum transfer qc ranging from 0.750 to 1.625 fm-1 were obtained. Using these values of SL(q) and the estimated ones found at q = 0.55 fm-1 and 0.65 fm-1, Ecoul = (1.928 ± 0.038 ± 0.026) MeV was derived for the total Coulomb energy. A number of methodological developments were made to reach a high accuracy of the experimental results. The analysis of the experimental Coulomb sum values has shown that the dependence SL(q) has a high sensitivity to the degree of clustering of the nuclei. The result of the comparison of the Coulomb energy for 7Li nucleus with the Coulomb energies for the 6Li and 4He nuclei – is consistent with the ratio 1/2(7Li)/1/2(6Li) = 0.948 ±0.008 (observed earlier in the experiment on the elastic electron scattering off the 7Li and 6Li nuclei); – leads to the conclusion that, within the two-cluster model of the 7Li nucleus (α + t), the effective linear size of the α-cluster should be larger than the one of the 4He nucleus. The experimental values of RL(qc,ω), SL(q) and Ecoul for the 7Li nucleus were obtained for the first time.
Coulomb sum and Coulomb energy of the 7Li nucleus
У дисертації наведені результати дослідження кулонової суми та кулонової енергії ядра 7Li на основі даних інклюзивного розсіяння електронів у широкому діапазоні початкових енергій Е0 та кутів розсіяння θ. У цих дослідженнях були здобуті значення поздовжньої функції відгуку RL(qc,ω) та кулонової суми SL(q) ядра 7Li у діапазоні постійних значень переданих імпульсів qc від 0.750 до 1.625 фм-1. Використовуючи ці значення SL(q), а також здобуті оцінки цієї величини при q = 0.55 фм-1 та 0.65 фм-1, з високою точністю була визначена повна кулонова енергія ядра 7Li, яка дорівнює Ecoul = (1.928 ± 0.038 ± 0.026) МеВ, де перша похибка статистична, а друга – систематична. Для того, щоб здобути з високою точністю експериментальні результати було розроблено низку методичних підходів. Проведений аналіз експериментальних значень кулонової суми довів, що залеж-ність SL(q) має високу чутливість до степеня кластеризації ядра. Порівняння кулонової енергії ядра 7Li з кулоновими енергіями ядер 6Li та 4Не – узгоджується з раніше спостережуваними в експерименті з пружного розсіян-ня електронів на ядрах 6Li та 7Li відношенням 1/2(7Li)/1/2(6Li) = 0.948 ±0.008; – приводить до висновку, що, в рамках двокластерної моделі ядра 7Li (α + t), ефективний лінійний розмір α-кластера більший за розмір вільного ядра 4Не. Експериментальні значення RL(qc,ω), SL(q) та Ecoul ядра 7Li здобуті вперше.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::NATURAL SCIENCES::Physics; ядро 7Li; інклюзивне розсіяння електронів; радіаційні та іонізаційні ефекти; поздовжня функція відгуку; кулонова сума; кулонова енергія; кластеризація ядер; 7Li nucleus; inclusive electron scattering; radiation and ionization effects; longitudinal response function; Coulomb sum; Coulomb energy; clustering of nuclei